Experimental Animal Models of Human Diseases An Effective Therapeutic Strategy - Bartholomew, Ibeh (IntechOpen, 2018)
The world has recorded losses in terms of human life as well as extensive time spent in experimentation with development of new drugs, elucidation of disease mechanism(s), and therapeutic agent discovery. Ethical and legal issues cojoin in slowing down scientific discoveries in medicine and biology. The past two (2) decades, therefore, have seen tremendous attempts that largely are successful in developing animal models with the characteristics of mimicking, approximating, or expressing transplanted human organs/tissues. These models or rather approaches seem to be fast, cost-effective, and easy to maintain compared to primates. This book is a collection of expert essays on animal models of human diseases of global interest. A visible objective of the book is to provide real-time experimental approach to scientists, clinicians, ethicists, medicolegal/medical jurisprudence workers, immunologists, postgraduate students, and vaccinologists and informative and multidisciplinary approach for the identification of new therapeutic targets and biomarkers using animal models as well as investigating the pathogenesis and therapeutic strategies of human diseases. An increased understanding of the genetic, molecular, and cellular mechanisms responsible for the development of human diseases has laid out the foundation for the development of rational therapies mainly with animal models.